CIVIL LIABILITY FOR DAMAGE CAUSED BY A ROBOT WHEN PERFORMING A MEDICAL PROCEDURE - Pichler, Davorin (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
Robots in medicine, unlike industrial automation, can be viewed as an extension or enhancement of human capabilities. The legitimacy of robotics in the health care system stems from the fact that its use increases the efficiency of the treatment process and improves the health of the individual. On the other hand, involving robots in the medical procedure brings a high degree of risk and liability for damage. Legal doubts that arises regarding the use of robots in medicine are related to civil liability for damage caused to the patient during the medical procedure. Related to that, it is necessary to determine the model of indemnity liability that applies to damages due to the action of robots in a medical procedure. Will a system of subjective liability based on guilt or a system of objective liability without determining the guilt of the injurer be applied? This issue is gaining in importance given the degree of autonomy of robots in performing medical procedures. The paper will emphasize the need for legislative intervention in the Croatian legal system in order to adapt to the growing use of robots in medicine. The paper will summarize the results of the analysis of the mentioned issues and offer possible solutions in court practice and legal dogmatics.